1989
DOI: 10.1159/000234953
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Experimental Allergic Encephalomyelitis with Complete Freund’s Adjuvant Is Unaffected by Prostaglandin Synthesis Inhibition

Abstract: Pretreatment with complete Freund’s adjuvant blended with aluminium hydroxide (ALU-CFA) prevents the clinical as well as histological manifestation of experimental allergic encephalomyelitis (EAE) in Lewis rats. Suppression of prostaglandin biosynthesis with the cyclooxygenase inhibitor piroxicam (10 mg/kg body weight) from day 2 before to day 17 after EAE induction could not restore responsiveness in pretreated animals. In contrast piroxicam increased ALU-CFA-induced suppression of autoantibodies against myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In a previous publication, we reported that the prophylactic application of piroxicam (Feldene®), a reversible inhibitor of cyclooxygenase, attenuated clinical signs of EAE, although the cellular infiltra tion of the central nervous system was not altered [3], The following investigation confirms these results and shows the effects of a therapeutic administration of piroxicam at the clinical and histological level. Pos sible reasons for the different effects of the prophy lactic and therapeutic treatment are discussed.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…In a previous publication, we reported that the prophylactic application of piroxicam (Feldene®), a reversible inhibitor of cyclooxygenase, attenuated clinical signs of EAE, although the cellular infiltra tion of the central nervous system was not altered [3], The following investigation confirms these results and shows the effects of a therapeutic administration of piroxicam at the clinical and histological level. Pos sible reasons for the different effects of the prophy lactic and therapeutic treatment are discussed.…”
Section: Introductionsupporting
confidence: 77%
“…EDl-positive cells in the circumference of the infiltrate were counted. b Significance of results was calculated using Wilcoxon's rank test [15], EAE, the permeability of the blood-brain-barricr is increased by the encephalogenic mixture, which allows hydrophilic molecules to enter the central nervous system [15], In a previous study [3], we reported that the clin ical signs of EAE were attenuated by the prophylactic administration of piroxicam. These results were con firmed by our experiments reported here.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 expression was also colocalized to iNOS expression, particularly in regions showing active demyelination, suggesting that COX-2 inhibitors could have therapeutic application in MS. As a result of these findings, recently developed COX-2 inhibitors, effective in the treatment of conditions such as inflammatory pain and rheumatoid arthritis, are now being investigated for a broader range of disease indications, including Parkinson's disease, ALS, stroke and AD. 62 In terms of disease-relevance to MS, nonselective COX inhibitors (BW755c, piroxicam, phenidone), as well as anti-PGE antibodies, have shown prophylactic effects in models of EAE, 60,[63][64][65] suggesting that the COX-2 component may play a prominent role in the inflammatory pathological cascade of MS. The results from the report, of CNS localization of COX-2 in the brains of MS patients and EAE-sensitized animals, highlights the potential importance of COX-2 in the pathogenesis of MS.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%